A food pyramid for adult patients with phenylketonuria and a systematic review on the current evidences regarding the optimal dietary treatment of adult patients with PKU. Issue 5 (May 2023) - Rondanelli, Mariangela; Porta, Francesco; Gasparri, Clara; Barrile, Gaetan Claude; Cavioni, Alessandro; Mansueto, Francesca; Mazzola, Giuseppe; Patelli, Zaira; Peroni, Gabriella; Pirola, Martina; Razza, Claudia; Tartara, Alice; et al.
Summary: Early dietary treatment is mind-saving in patients with phenylketonuria. A "diet-for-life" is advocated, aimed to prevent effects of chronic exposure to hyperphenylalaninemia. While adherence to diet is significant during childhood as patients are followed-up at specialized metabolic centers, during adolescence and adulthood percentage of patients discontinuing diet and/or lost at follow-up is still high. The process of passing skills and responsibilities from pediatric team to adult team is defined "transition". The goal of transition clinics is to set up specific multidisciplinary care pathways and guarantee continuity of care and compliance of patients to care. In 2017, "The complete European guidelines on phenylketonuria" were published. These guidelines, however, do not provide an easy way to illustrate to adult patients how to follow correct dietary approach. The purpose of this review is to evaluate current evidence on optimum dietary treatment of adults with phenylketonuria and to provide food pyramid for this population. The pyramid built shows that carbohydrates should be consumed every day (3 portions), together with fruits and vegetables (5 portions), extra virgin olive oil, and calcium water (almost 1 L/day); weekly portions can include 150 g potatoes walnuts and hazelnuts (20 g). At top of pyramid, there are two pennants. The green means that, based on individual metabolic phenotype and daily phenylalanine tolerance, patients need personalized supplementation (specific phenylalanine free amino acid mixtures, vitamins and omega 3 fatty acids); the one red indicates foods that are banned from diet (aspartame and protein foods exceeding individual dietary phenylalanine tolerance).